Between Orientalism and Westernization: Belly Dance as a Transnational American Studies Case. (2nd October 2015) - Gurel, Perin
Abstract : In the last decade, American women's rising interest in belly dance has drawn the critical attention of American studies scholars. Americanists have traced the transnational development of the dance complex and skilfully critiqued the imperialist politics that are manifest in Western belly dance practice alongside the rhetoric of feminist liberation. With its apparently feminine, mysterious, and exotic qualities, belly dance seems to make a casebook study for Orientalism. Therefore, scholars have tended to view belly dance through this scholarly frame. Yet, if considering only US contexts, utilizing only English-language resources, and only wielding the Western theoretical cannon, even transnational American studies scholarship risks replicating the Orientalist knowledge practices it identifies and condemns in Western women's belly dance practice and commentary. This essay argues that, despite the conspicuousness of its impact, Orientalism has not been the only civilizational logic operating in the transnational construction of belly dance. Throughout the nineteenth and twentieth centuries, the dance and its meanings were modified also by the East's perceptions of the West and official attempts to counter the exotic through Westernization. Utilizing Turkish and English sources and participant observation in the United States and Turkey, I compare the contemporary American meanings of the dance complex to its uses in Turkey. I foreground the predominant role played by the male belly, marginalized in American studies of the dance complex, and show how the complex local category of Westernization operates in an uneasy dialectic with Orientalism. This research suggests that the transnational, with its attention to the movement of people, products, and ideas across nation-state borders, must be balanced with the comparative, with attention to cultural formations that do not translate easily across cultures.